Cortical development of AMPA receptor trafficking proteins - Murphy, Kathryn M.; Tcharnaia, Lilia; Beshara, Simon; Jones, David G. (Frontiers in Molecular Neuroscience, 2012)
AMPA-receptor trafficking plays a central role in excitatory plasticity, especially during development. Changes in the number of AMPA receptors and time spent at the synaptic surface are important factors of plasticity that directly affect long-term potentiation (LTP), long-term depression (LTD), synaptic scaling, and the excitatory-inhibitory (E/I) balance in the developing cortex. Experience-dependent changes in synaptic strength in visual cortex (V1) use a molecularly distinct AMPA trafficking pathway that includes the GluA2 subunit. We studied developmental changes in AMPA receptor trafficking proteins by quantifying expression of GluA2, pGluA2 (GluA2serine880), GRIP1, and PICK1 in rat visual and frontal cortex. We used Western Blot analysis of synaptoneurosome preparations of rat visual and frontal cortex from animals ranging in age from P0 to P105. GluA2 and pGluA2 followed different developmental trajectories in visual and frontal cortex, with a brief period of over expression in frontal cortex. The over expression of GluA2 and pGluA2 in immature frontal cortex raises the possibility that there may be a period of GluA2-dependent vulnerability in frontal cortex that is not found in V1. In contrast, GRIP1 and PICK1 had the same developmental trajectories and were expressed very early in development of both cortical areas. This suggests that the AMPA-interacting proteins are available to begin trafficking receptors as soon as GluA2-containing receptors are expressed. Finally, we used all four proteins to analyze the surface-to-internalization balance and found that this balance was roughly equal across both cortical regions, and throughout development. Our finding of an exquisite surface-to-internalization balance highlights that these AMPA receptor trafficking proteins function as a tightly controlled system in the developing cortex.